Malaysia School Leadership Crisis Covid-19: Conventional To Adaptive Leadership - Don, Yahya (Universitas Serambi Mekkah, 2020)
This paper work is discussed about Malaysia school leadership crisis in pandemic Covid 19. The impact of the Movement Control Order (MCO)/Targeted Enhanced Movement Control Order (TEMCO) and online learning, is increasing anxiety, stress and depression among individuals teachers, parents and students in Malaysia school. They need a school leader who is adequately equipped, skilled and supported. There are many different leadership theories, and transformational leadershiptheories ismost important before 2020, particularly in the context of education, instructional leadership style. In Malaysia schools, Adaptive Leadership might be the most relevant and powerful leadership style. Adaptive Leadership is a practical leadership framework that helpsindividuals and organizations adapt and thrive in challenging environments. Adaptive leaders create conditions that enable dynamic networks and environments to achieve common goals in an environment of uncertainty. Adaptive Leadership focuses on four dimensions; navigating schoolenvironments; leading with empathy; learning through self-correction and reflection-creating win-win solutions. It is being able, both individually and collectively, to take on the gradual but meaningful process of change. This paper also discussed an emerging role and challenging of the school leadersand teachers required to transform the leadership style in the Pandemic Covid 19, Adaptive Leadership is purposeful evolution in Malaysia school system.Keyword: Educational Leadership, Adaptive Leadership, Pandemic Covid 19